Isolasi dan Identifikasi Bakteri Salmonellasp dan Serratia sp Pada Eksoskeleton Lalat Hijau (Chrysomya megacephala) - Rizal Maarif Rukmana; Rika Siwi Utami (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Chrysomyamegacephala is one species that often found around humans, especially in Traditional Markets. Chrysomyamegacephala is one vector of various diseases caused by: bacteria, parasites and helmin. The purpose of this study was to determine whether the exoskeleton of the Chrysomyamegacephala carries the bacteria Salmonellasp and Serratia sp. The method used in catching the Chrysomyamegacephala is by using adhesive bait paper. Number of Chryosomya megacephala samples is 30. Chryosomya megacephalaare then identified. The next step is the isolation of the bacterium Salmonella sp and Serratiasp in the Chrysomyamegacephala using Salmonella Shigella Agar (SSA) and Endo Agar (EA). Identification is done by observing colonies, biochemical tests and gram staining. The results obtained were found in Serratiasp on the exoskeleton of the Chrysomyamegacephalaas much as 90%. Salmonellasp bacteria identified 63.33% on the exoskeleton of the Chrysomyamegacephala. Salmonellasp and Serratiasp bacteria identified in the Chrysomyamegacephala are 30%.Chrysomyamegacephala flies obtained from the Surakarta Mojosongo Market are accepted as vectors of Salmonellasp and Serratia sp.